Space QUEST mission proposal: experimentally testing decoherence due to gravity - Siddarth Koduru Joshi; Jacques Pienaar; Timothy C Ralph; Luigi Cacciapuoti; Will McCutcheon; John Rarity; Dirk Giggenbach; Jin Gyu Lim; Vadim Makarov; Ivette Fuentes; Thomas Scheidl; Erik Beckert; et al. (New Journal of Physics, 2018)
Models of quantum systems on curved space-times lack sufficient experimental verification. Some speculative theories suggest that quantum correlations, such as entanglement, may exhibit different behavior to purely classical correlations in curved space. By measuring this effect or lack thereof, we can test the hypotheses behind several such models. For instance, as predicted by Ralph et al [ 5 ] and Ralph and Pienaar [ 1 ], a bipartite entangled system could decohere if each particle traversed through a different gravitational field gradient. We propose to study this effect in a ground to space uplink scenario. We extend the above theoretical predictions of Ralph and coworkers and discuss the scientific consequences of detecting/failing to detect the predicted gravitational decoherence. We present a detailed mission design of the European Space Agency’s Space QUEST (Space—Quantum Entanglement Space Test) mission, and study the feasibility of the mission scheme.